Resilience in Adolescent Victims of Bullying: The Role of Emotion Regulation and Social Support - Subagio, Naomi Aryandini; Virlia, Stefani (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Bullying experienced by adolescents has a negative impact, which necessitates the development of high levels of resilience to address and grow from traumatic experiences. Key influencing factors include emotion regulation and social support. Therefore, this study aimed to investigate the impact of two emotion regulation strategies and social support on resilience of adolescent victims of bullying. This was a quantitative study with a correlational design, involving 612 adolescent victims of bullying aged 13-15 years from junior high schools in Surabaya. The results showed a significant effect (p